THE APPLICATION OF SCANNING ELECTRON MICROSCOPY USING ENERGY- AND WAVELENGTH DISPERSIVE SPECTROMETERS FOR CHEMICAL DATING OF URANIUM MINERALIZATION ON THE EXAMPLE OF CARBONACEOUS SHALES OF THE DABANZHALGA SUITE (EAST SAYAN) - D. K. Belyanin; N. S. Karmanov; E. V. Airiyants; S. M. Zhmodik (Геодинамика и тектонофизика, 2022)
On the one hand, the widespread use of electron microprobe analysis in the version of a scanning electron microscope (SEM) equipped with an energy dispersive spectrometer (EDS) and, on the other hand, the comparability of the metrological characteristics of the EDS and wavelength dispersive spectrometry (WDS) in the case of determining the major components of minerals are a favourable background for investigating the possibility of using SEM-EDS for chemical dating of uranium mineralization. Carbonaceous-siliceous formations of the Dabanzhalga suite are widespread in carbonate deposits of the Lower Paleozoic in the Oka structural-formational zone of the East Sayan and represent deep-water deposits of the back-arc basin. All varieties of carbonaceous-siliceous rocks of the Dabanzhalga suite are characterized by increased U, Au, Ag, Pt, Pd, Mo, V, P, Cu. Their amounts are 5–10 times higher than those for other black shale deposits of the Eastern Sayan. Uranium forms its minerals – uraninite and brannerite, in association with carbonaceous matter and sulfides, and is also part of anhydrous phosphates – xenotime, monazite. The paper presents data on the composition and dating of brannerite and uraninite in samples of carbonaceous-siliceous shale sampled at three sites: Uber-Zhadoy, Deed-Khara-Zhalga and Erye-Khara-Zhalga. The obtained estimates of the isochronous dates of uraninite and brannerite grains for these areas are 523±26, 506±10, and 511±17 Ma, respectively. It was shown that these dates could be compared with the age of metamorphism at the Sukhoi Log deposit, estimated using modern methods of isotope geochronology. It should be noted that the average estimates of the dates of uraninite and brannerite in all studied areas of the Dabanzhalga suite are lower than the corresponding estimates of the isochronous date, which is probably due to the partial loss of radiogenic lead. For the Uber-Zhadoy site, a comparison of the EDS and WDS data was carried out, and it was shown that when using the EDS data, there is an underestimation of the Pb content in uraninite, and, as a consequence, an underestimation of the age of uraninite.